2015
DOI: 10.18343/jipi.20.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Parasitic in Eels (Anguilla spp.) from Lindu Lake, Central Sulawesi

Abstract: ABSTRAKInfeksi protozoa pada ikan sidat (Anguilla spp.) asal Danau Lindu memengaruhi berat ikan dan kesehatan ikan. Pemeriksaan parasit pada ikan sidat, yaitu koleksi ikan sidat, pemeriksaan ikan, observasi, pengukuran, identifikasi parasit, dan pewarnaan protozoa menggunakan giemsa. Keragaman protozoa parasitik adalah Myxidium sp., Myxobolus sp., Chilodonella sp., Ceratomyxa sp., Balantidium sp., Henneguya sp., dan Glugea sp. Prevalensi tertinggi, yaitu Myxidium sp. sebesar 77 pada ikan sidat dan tidak ada p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The results showed that fish from Kupang, Indonesia could cross to Australia but no adult fish moved from Australia to Kupang. The article by Amir et al (2016) and Jabal et al (2020) provides interesting fact regarding the spread of A. simplex. The Anisakiosis case reported by Amir et al (2016) is intriguing since the patient disclosed a history of consuming Empurau fish (Tor tambroides) sushi at one of the Japanese restaurants in Kuala Lumpur two days before to a clinical presentation.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that fish from Kupang, Indonesia could cross to Australia but no adult fish moved from Australia to Kupang. The article by Amir et al (2016) and Jabal et al (2020) provides interesting fact regarding the spread of A. simplex. The Anisakiosis case reported by Amir et al (2016) is intriguing since the patient disclosed a history of consuming Empurau fish (Tor tambroides) sushi at one of the Japanese restaurants in Kuala Lumpur two days before to a clinical presentation.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…It was determined to be an A. simplex using COX2 mtDNA PCR scanning, provided more evidence of A. simplex presence in Malaysia. Does this suggest that anadromous fish can spread Anisakis to fish in fresh waters and what is the process of its transmission, considering the fact that of research Jabal et al (2020) found that eels (Anguilla spp.) in the Lake Lindu were infected with Anisakis.…”
Section: Molecular Identificationmentioning
confidence: 99%